Perception of pregnant women about self-care and maternal care - Silveira, Rosimeire Aparecida Monteiro (2016)
Objective: to understand the perception of self-care and maternal care in the discourse of pregnant women under the psychosocial perspective. Methods: qualitative study with data collection performed through a semi structure interview with ten pregnant women. The technique of content analysis, associated with the computer program Atlas TI, was used. Results: two analytical categories were identified, self-care: taking care of one’s own body and maternal care. Postmodern thinking influenced the self-care actions of pregnant women. However, maternal care was not directly influenced and pregnant women showed indicators of primary maternal concern, such as feelings and attitudes that provide the baby with comfort, protection and comfort. Conclusion: the self- care actions performed by the pregnant women showed concern about the aesthetic appearance at the expense of attitudes to preserve health and quality of life.